2023
DOI: 10.3390/ijerph20053863
|View full text |Cite
|
Sign up to set email alerts
|

Healthy City Community Space-Oriented Structural Planning and Management Optimization under COVID-19

Abstract: This work studies ways of Healthy City Construction (HCC) and Urban Governance Optimization (UGO) during the COVID-19 pandemic. The specific urban community space planning structure is proposed following a literature review on the healthy city’s theoretical basis and historical development. Then, the proposed HCC-oriented community space structure is tested by surveying residents’ physical and mental health and infectious risk using a questionnaire survey and Particle Swarm Optimization (PSO). Specifically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Many complex factors determine the location of an effective health facility, including population, existing service levels, and current and future demand, and these must be carefully considered [ 14 ]. Of the various criteria for determining the location of health facilities, surveys have shown that the distance to health facilities is a key factor for the community in choosing health facilities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many complex factors determine the location of an effective health facility, including population, existing service levels, and current and future demand, and these must be carefully considered [ 14 ]. Of the various criteria for determining the location of health facilities, surveys have shown that the distance to health facilities is a key factor for the community in choosing health facilities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%